Prevalence of Developmental Dyslexia among Primary School Children in Iran: A Systematic Review and Meta-Analysis - Farhad Sakhai; Samira Mazaheri; Golnoosh Golmohammadi; Faezeh Asadollahpour (Iranian Journal of Psychiatry)
Objective: Developmental dyslexia is a specific learning disability related to reading that often leads to lifelong challenges. Accurate prevalence estimates are essential for the timely diagnosis, intervention, and formulation of appropriate educational policies. This systematic review and meta-analysis aimed to provide a reliable estimate of the prevalence of developmental dyslexia in primary school students in Iran. Method: We conducted a comprehensive search of international databases, including PubMed, Web of Science, and Scopus, alongside national databases such as SID and Magiran, using relevant search terms from 1991 to April 2024. Two researchers independently assessed the articles for the risk of bias using the Hoy checklist and extracted the data. Subgroup meta-analysis examined variations in prevalence across different subgroups. Results: A total of 18 studies, comprising 28,952 participants, were included. The overall prevalence of developmental dyslexia was 5.7% (95% CI: 4.5%-6.9%), with a higher prevalence observed in boys (7.5%, 95% CI: 5.8%-9.2%) compared to girls (4%, 95% CI: 3%-5%). Subgroup analysis revealed a statistically significant impact of diagnostic material on prevalence estimates, with informal reading tests reporting a prevalence of 3.4% (95% CI: 2.4%-4.4%) and the screening inventory reading test showing 8.8% (95% CI: 4.5%-13.2%) (P = 0.002). Prevalence also varied by sample size, with smaller studies (< 500 participants) reporting a prevalence of 6.8% (95% CI: 5%-8.6%) compared to larger studies (>2000 participants) at 3.9% (95% CI: 2.3%-5.4%) (P = 0.034). Most studies (66.7%) had sample sizes under 2000 participants. Conclusion: This systematic review and meta-analysis indicate that developmental dyslexia affects 5.7% of Iranian primary school students, with boys being more affected than girls. These findings highlight the urgent need for standardized diagnostic criteria and evidence-based interventions to enhance early identification and support for students with dyslexia. Addressing these gaps is essential for improving educational outcomes and guiding effective policy planning.